Religious Values of Youth within the Framework of the Sociology of Culture - Artukhov, Andrey V. (2022)
In a situation of paradigm pluralism of modern sociology, the selection of certain provisions for the formation of a theoretical framework always causes certain difficulties and problems. On the one hand, there is a clear division of sociological knowledge along the line of the classical – non-classical, and on the other hand, in the present conditions this division looks somewhat artificial and, according to many analysts, should be replaced by the integration of approaches, theories, and concepts, the creation of an integrative paradigm. Therefore, considering the sociological heritage and new developments, it is necessary to select those groups of theoretical propositions that will help reveal the diversity of values in empirical research. The novelty of the research is determined by the existence of a certain hierarchy in the value system. As part of any value system, one can distinguish, first of all, dominant values. The authors show that the system of values determines the criteria recognised by society, based on which control over the activities of people is carried out and their behaviour is regulated, that is, it is the system of values that ensures civil order. It acts as a theoretical framework for social activity. Authors determine that the value system regulates the behaviour of people in society and directs it in the proper, correct direction. It acts as a guideline when choosing a method of action, forms goals and leads to their achievement. The practical significance of the research is determined by the fact that each culture creates its individual system of value guidelines, which serve as a kind of model, determine the direction of the actions of a person or the entire society, that is, values of a certain kind of motivators of actions